Association Between Smoking and Premenstrual Syndrome: A Meta-Analysis - Choi, So Hee; Hamidovic, Ajna (Frontiers in Psychiatry, 2020)
Results of basic science studies demonstrate shared actions of endogenous neuroactive steroid hormones and drugs of abuse on neurotransmission. As such, premenstrual syndrome (PMS) may be associated with smoking, however, results from studies examining this relationship have been mixed. PMS diagnosis, according to the Diagnostic and Statistical Manual of Mental Disorders 5 (DSM-5), is made when, between 1 and 4 affective, behavioral or physical symptoms are experienced specifically in the premenstruum. Following PRISMA guidelines, we extracted unique studies examining the relationship between smoking and PMS. We used the escalc () function in R to compute the log odds ratios and corresponding sampling variance for each study. We based quality assessment on the nature of PMS diagnosis and smoking estimation, confounding adjustment, participation rate and a priori specification of target population. Our final sample included 13 studies, involving 25,828 study participants. Smoking was associated with an increased risk for PMS (OR=1.56, (95% CI:1.25-1.93), p<.0001). Stratified by diagnosis, the effect size estimate was higher for Premenstrual Dysphoric Disorder (PMDD) (OR=3.15, (95% CI:2.20-4.52), p<.0001) than for PMS (OR=1.27 (95% CI:1.16-1.39), p<.0001). We review some of the basic mechanisms for the observed association between smoking and PMS. Given nicotine’s rewarding effects, increased smoking behavior may be a mechanism to alleviate affective symptoms of PMS. However, smoking may lead to worsening of PMS symptoms because nicotine has effects on neurocircuitry that increases susceptibility to environmental stressors. Indeed, prior evidence shows that the hypothalamic-pituitary-adrenal (HPA) axis is already sub-optimal in PMS, hence, smoking likely further deteriorates it. Combined, this complicates the clinical course for the treatment of both PMS and Tobacco Use Disorder in this population.